THE INTEGRATION MODEL OF KNOWLEDGE AT UIN BANDUNG: FROM THE WAHYU MEMANDU ILMU PARADIGM TO RAHMATAN LIL ‘ALAMIN - Supiana; Afnie Rizky Nurkamaliyah; Nenden Ahadiah Halimah; Nirwati (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
The Wahyu Memandu Ilmu (WMI) paradigm promoted by UIN Bandung represents a model of knowledge integration that positions revelation as the epistemological foundation and scientific inquiry as the medium for academic development. This study aims to analyze the implementation of WMI by emphasizing Rahmatan lil ‘Alamin (RLA) as an axiological orientation manifested through institutional governance, academic policies, and impact-based evaluation mechanisms. The research employs a qualitative approach with a descriptive-analytical design, examining policy documents, curricula, and the practices of the university’s Tri Dharma at UIN Bandung. The findings indicate that epistemic integration between revelation and scientific knowledge has the potential to strengthen Islamic relevance and enhance academic responsiveness to global challenges. However, the effectiveness of RLA as a scholarly praxis requires the strengthening of institutional capacity, interdisciplinary collaboration, and measurable evaluation indicators to ensure that the values of rahmatan are concretely realized in campus activities.